2021
DOI: 10.1136/jnnp-2021-326708
|View full text |Cite
|
Sign up to set email alerts
|

Functional (psychogenic non-epileptic/dissociative) seizures: why and how?

Abstract: Functional seizures (FS) known also as psychogenic non-epileptic seizures or dissociative seizures, present with ictal semiological manifestations, along with various comorbid neurological and psychological disorders. Terminology inconsistencies and discrepancies in nomenclatures of FS may reflect limitations in understanding the neuropsychiatric intricacies of this disorder. Psychological and neurobiological processes of FS are incompletely understood. Nevertheless, important advances have been made on underl… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 164 publications
0
14
0
Order By: Relevance
“…Nevertheless, FS lie at the diagnostic interface of neurology and psychiatry, and research should therefore encompass a holistic, cognitive neuroscientific approach to these embodied symptoms. Indeed, this approach is reflected in recent, expert led reviews of the potential mechanisms underlying FS [5]. However, one factor that has been neglected in these reviews is joint hypermobility, which has been shown to be associated with several neuropsychiatric disorders [6,7].…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, FS lie at the diagnostic interface of neurology and psychiatry, and research should therefore encompass a holistic, cognitive neuroscientific approach to these embodied symptoms. Indeed, this approach is reflected in recent, expert led reviews of the potential mechanisms underlying FS [5]. However, one factor that has been neglected in these reviews is joint hypermobility, which has been shown to be associated with several neuropsychiatric disorders [6,7].…”
Section: Introductionmentioning
confidence: 99%
“…7,14 Consequently, several studies have explored how these risk factors interact in the development of FDS as predisposing, precipitating, or perpetuating factors. 3,8,15 Unfortunately, the multifactorial etiology and complex interactions between different factors make it difficult to devise a unitary etiopathological model or to devise treatment manuals. 3,8,15 The diagnosis of FDS was long based on the exclusion of epilepsy.…”
Section: Introductionmentioning
confidence: 99%
“…3,8,15 Unfortunately, the multifactorial etiology and complex interactions between different factors make it difficult to devise a unitary etiopathological model or to devise treatment manuals. 3,8,15 The diagnosis of FDS was long based on the exclusion of epilepsy. Recent texts have emphasized the importance of "positive" diagnostic criteria, emphasizing what characterizes FDS disorders themselves rather than what these disorders lack in comparison to epilepsy.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations